Comparative Study of Laser- attenuated and Gamma attenuated irradiated larval Vaccines of Dictyocaulus filaria in goats. - K., AL- Mashhadani, F.J.; G, AL-Samarrae, S.A. (The Iraqi Journal of Veterinary Medicine, 2021)
A comparative trial between the effect of 3rd stage Dictyocaulus filaria larval vaccine attenuated by continuous emission of visible Helium – Neon Laser of ImW and wave length of ( 632.8 ) nm of (5) minutes exposure that of gamma attenuated larvae at 0.5 k. gray ( Co as radiation Source ) was designed. Each of the two attenuated larval vaccines was given to a group of ( 5 ) kids each . Double immunization doses at ( 35 ) days interval from each vaccine were given orally. The first dose contained ( 1000 ) larvae and the second one ( 2000 ) for each . A challenge dose of ( 100 ) non- irradiated larvae /kg body weight was given after ( 5 ) week to the vaccinated groups and a control non- vaccinated (5 kids ) 3rd group. All animals were slaughtered after 6 weeks post challenge. Results showed that both vaccines revealed 80.7% and 78.1% protection respectively for worm burden as compared to control. Laser attenuated vaccine exhibited a statistically significant inhibition in the fecundity of female worms and larvae secretion in faeces in comparison with the gamma irradiated vaccine.